2019
DOI: 10.1103/physrevb.100.115406
|View full text |Cite
|
Sign up to set email alerts
|

DC spin generation by junctions with AC driven spin-orbit interaction

Abstract: An unbiased one-dimensional weak link between two terminals, subjected to the Rashba spin-orbit interaction caused by an AC electric field which rotates periodically in the plane perpendicular to the link, is shown to inject spin-polarized electrons into the terminals. The injected spin-polarization has a DC component along the link and a rotating transverse component in the perpendicular plane. In the low rotation-frequency regime, these polarization components are proportional to the frequency. The DC compon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…(34) and Eq. (35). Finally, we compare the Floquet result for AC charge current with our analytical prediction both in the low and the high-frequency regimes.…”
Section: Simulating the Dynamical Spin-transistor Functionalitymentioning
confidence: 84%
See 1 more Smart Citation
“…(34) and Eq. (35). Finally, we compare the Floquet result for AC charge current with our analytical prediction both in the low and the high-frequency regimes.…”
Section: Simulating the Dynamical Spin-transistor Functionalitymentioning
confidence: 84%
“…Here we sketch the derivation of the expressions (34) and (35) for the AC spin/charge current using the Landauer-Büttiker formalism. We start with the charge/spin current operator.…”
Section: Spin and Charge Current Calculation In The Landauer-büttiker...mentioning
confidence: 99%
“…However, the spin splitting that could facilitate the creation of polarized currents cannot, in principle, be produced by the unique action of SOC, because the system possess states with opposite spins and the same energy due to Kramer's degeneracy [16], a result of time reversal symmetry [9]. Magnetic fields, magnetic materials, and the injection of spin-polarized currents [17][18][19][20][21][22][23][24][25][26][27] or time-dependent Hamiltonians [28] have been used to break this symmetry and generate or manipulate spin-polarized currents. To obtain this result in non-magnetic materials, or without applying an external magnetic field, several systems have been proposed, such as point contact [29,30], graphene nanostructures [31], planar systems with SOC and corrugated graphene nanoribbons [32][33][34], or even creating spin-dependent chemical potentials by microwave irradiation [35].…”
Section: Introductionmentioning
confidence: 99%
“…Coherent electronic transport in response to periodic modulations of the shape of quantum dots or of other potential parameters of mesoscopic junctions has been attracting considerable interest [17,18] following the seminal paper by Thouless [19], who showed that a slow periodic variation of the potential landscape may yield quantized and non-dissipative particle transport in unbiased junctions-a phenomenon termed "adiabatic quantum pumping". Adiabatic pumping of spin currents resulting from periodic modulations of the shape of a spinorbit coupled junction has been discussed as well [20], also as a result of temporal modulations of the Rashba interaction [21][22][23][24]. However, the possibility to induce a DC particle current by such modulations in the absence of a bias voltage was not considered.…”
mentioning
confidence: 99%